Role of metal foam on ice storage performance for a cold thermal energy storage (CTES) system. (April 2020) - Yu, Cheng; Peng, Quan; Liu, Xiangdong; Cao, Peng; Yao, Feng
Highlights: A cold energy storage model is developed and experimentally verified. Transient temperature distribution and solid–liquid interface evolution are investigated. Metal foam induces stronger temperature uniformity and hence faster solidification rate. Abstract: The cold thermal energy storage (CTES) is of great significance for the sake of decline of fossil energy usage. However, there exhibits a low energy charging and discharging efficiency, due to the poor thermal conductivity of phase change material (PCM). In this context, the metal foam is utilized to improve the ice storage performance of the CTES device in this paper. The solidification performance of PCM in a horizontal shell-tube CTES system with fins is numerically studied with consideration of natural convection. The ice front evolutions and the dynamic temperature distribution for the case with metal foam is analyzed and compared with these without metal foam. Moreover, the influence of the porosity on the ice storage performance for the CTES system with metal foams is analyzed as well. The results imply that the addition of metal foam effectively improves the thermal performance of the CTES system, the distribution of the temperature in the shell-tube CTES system is more uniform and the freezing speed of PCM is faster due to coupled effects of thermal conduction enhancement and the suppression of the natural convection. The porosity of the metal foam plays an essential role in the ice storage performance of the CTES system. The smaller porosity of the metal foam induces faster freezing speed and more uniform temperature distribution. Therefore, a smaller porosity is recommended for faster energy discharging rate in practical engineering applications.